Physicochemical and functional enhancement of κ-carrageenan films with olive oil for biodegradable active food packaging - Marshidi, Puteri Alia; Foong, Han Lyn; Zainal Abedin, Nur Hanani (John Wiley and Sons, 2025)
This study addresses the need for sustainable and functional food packaging materials by exploring the incorporation of olive oil into κ-carrageenan films to enhance their physicochemical and antioxidant properties. Olive oil, known for its hydrophobic and bioactive characteristics, was added at concentrations of 1.5%, 3.0%, and 4.5%. At 4.5%, olive oil significantly (p<0.05) reduced water solubility of κ-carrageenan films by 26%, while improving UV light barrier properties at 200, 280, and 400 nm. However, it also increased water vapor permeability and opacity. Mechanical testing revealed a trade-off, with decreased tensile strength but a significant (p<0.05) increase in elongation at break, improving flexibility. Thermal properties of the films were analyzed using differential scanning calorimetry and the results indicated an elevation in melting temperature, peaking at 104.75 °C for films with 4.5% olive oil. Confocal laser scanning microscopy (CLSM) revealed that a 1.5% oil concentration produced the most homogeneous structure. Antioxidant analysis showed increased (p<0.05) total phenolic content (22.02 mg GAE/100g at 4.5% olive oil), with a corresponding rise (p<0.05) in DPPH radical scavenging activity and ferric reducing antioxidant power (FRAP). These findings highlight the dual role of olive oil as a mechanical plasticizer and an antioxidant, providing new insights into the development of biodegradable κ-carrageenan-based films for active food packaging applications.